Imaging for Epilepsy Surgery - Chavakula, Vamsidhar; Cosgrove, G. Rees (Seminars in Neurology, 2017)
Successful epilepsy surgery requires accurate localization of the zone of seizure onset and its complete removal without causing any permanent neurological deficits. While clinical semiology, ictal EEG recordings, and neuropsychological testing are all useful in defining the seizure focus, advanced neuroimaging has emerged as the most important localizing tool. Structural and metabolic imaging can now identify subtle cortical abnormalities that if consistent with other presurgical evaluation investigations, can improve surgical outcomes. Functional imaging can also be helpful in defining eloquent cortex and its relationship to planned surgical resection sites to reduce the risk of neurological impairment. This article explores several advanced neuroimaging techniques and their role in the surgical treatment of epilepsy.
Keywords: epilepsy; MRI; PET; EEG; surgery